The Role of Cognitive Offloading in Mediating the Effects of Creativity, Artificial Intelligence, and Critical Thinking on Higher Order Thinking Skills - RZ Abdul Aziz; Anton Setiawan (SISTEMASI, 2026)
This study investigates the role of cognitive offloading in mediating the effects of creativity, artificial intelligence (AI), and critical thinking on Higher Order Thinking Skills (HOTS). A quantitative design using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied. The respondents were undergraduate students from three universities in Indonesia (Universitas Lampung, Universitas Aisyah Pringsewu, and IIB Darmajaya). Using the Slovin formula with a 10% margin of error, 295 questionnaires were distributed, and 202 valid responses were obtained from students who reported frequent use of AI in academic activities. The findings indicate that creativity, AI, and critical thinking positively and significantly influence cognitive offloading. Critical thinking and cognitive offloading significantly affect HOTS, while creativity and AI do not show significant direct effects on HOTS. Cognitive offloading fully mediates the effects of creativity and AI on HOTS and partially mediates the effect of critical thinking on HOTS. The structural model explains 51.9% of the variance in HOTS (R² = 0.519). These results highlight that AI integration alone does not automatically enhance higher-order thinking; instead, structured cognitive regulation strategies—particularly cognitive offloading and critical thinking—are essential for optimizing AI-based learning in higher education.